Communally established cattle feedlots as a sustainable livelihood option for climate change resilience and food security in sub-Saharan Africa: a systematic review - Slayi, Mhlangabezi; Zhou, Leocadia; Nyambo, Patrick; Jaja, Ishmael Festus; Muchaku, Shadreck (Frontiers in Sustainable Food Systems, 2024)
Climate change poses a significant threat to agriculture and livestock production in sub-Saharan Africa, a region heavily reliant on livestock for smallholder farmers’ livelihoods. This systematic review investigates the potential of communally established cattle feedlots as a sustainable strategy to address the interconnected challenges of climate change resilience and food security in the area. The review focuses on the intensification of climate change, marked by rising temperatures and altered precipitation patterns, posing a direct threat to the livelihoods of millions in the region. Conducting a systematic literature review, we meticulously analyzed 72 articles that centered on communally established cattle feedlots in sub-Saharan Africa. The inclusion criteria considered studies within the context of climate change resilience and food security, utilizing both qualitative and quantitative methodologies. Published articles, grey literature, and relevant reports were systematically sourced from academic databases such as PubMed, Scopus, Google Scholar and Web of Science, complemented by manual searches of journals, conference proceedings, and organizational websites. The synthesis of findings reveals a nuanced landscape of successes and challenges associated with communal feedlots. Through a narrative synthesis, studies were categorized based on key themes, unraveling the impact of communal feedlots on livestock health, economic viability, and socio-economic dynamics. The review highlights the role of communal feedlots in mitigating climate-related shocks, enhancing livestock productivity, and fostering economic opportunities for smallholder farmers. However, challenges related to land tenure, community engagement, and resource allocation emerged as critical considerations. In conclusion, communally established cattle feedlots offer a holistic and sustainable approach to address climate change challenges in sub-Saharan Africa.